Honeysuckle Creek - Tink, Andrew (University of New South Wales Press, 2019)
Honeysuckle Creek reveals the pivotal role that the tracking station at Honeysuckle Creek, near Canberra, played in the first moon landing. Andrew Tink gives a gripping account of the role of its director Tom Reid and his colleagues in transmitting some of the most-watched images in human history as Neil Armstrong took his first step. Part biography and part personal history, this book makes a significant contribution to Australia's role in space exploration and reveals a story little known until now. As Christopher Columbus Kraft Jr, the director of flight operations for Apollo 11, acknowledged.